CARING FOR CLIENTS WITH ALZHEIMER'S DISEASE AND RELATED DEMENTIAS: PREPARING HOME HEALTH AIDES. (11th November 2018) - Jared, M; Cortes, T; Levine, J; Graham, K; Torres, A; Powell, P
Abstract: In partnership with PHI, we created a 4-hour in-person educational course on Caring for Clients with Alzheimer's Disease and Related Dementias. From January through June of 2017, 1, 123 Home Health Aides at R.A.I.N. Home Health Care in the Bronx, NY took the course. Preliminary data analysis showed that the mean post-test score was 91% (N=1028). Eighty two percent of the participants (N=999) reported that their confidence level was "very or completely confident" after completing the education.